CHARACTERISTICS OF MANAGING THE ACTIVITY OF BUILDING MATERIALS MANUFACTURING ENTERPRISES - Ubaidullaev, Takhirjan Abdullajanovich; Ibrogimov, Sherzodbek Halimjon ogli (Educational Research in Universal Sciences, 2023)
This article characteristics of the management of construction materials production enterprises light up given.